Long-Term Effects of Straw and Straw-Derived Biochar on Humic Substances and Aggregate-Associated Humic Substances in Brown Earth Soil - Sun, Qiang; Yang, Xu; Meng, Jun; Lan, Yu; Han, Xiaori; Chen, Wenfu; Huang, Yuwei (Frontiers in Environmental Science, 2022)
Turning maize straw into biochar is useful for improving soil fertility and mitigating climate change. However, the difference between straw and straw-derived biochar on soil aggregate associated humic substances has not been sufficiently studied in brown earth soil. The objective of this study was to investigate how different straw management practices affect soil humic substances and aggregate-associated humic substances in the field. As such, an eight-year study (2013–2020) was conducted on brown earth in Northeast China. Three treatments were applied: 1) CK, in which only chemical fertilizer was applied every year; 2) BC, in which biochar was applied at a rate of 2.625 t ha−1 (the same rate of chemical fertilizer as that in the CK was applied); 3) SR, in which straw was returned at a rate of 7.5 t ha−1 (the same rate of chemical fertilizer as that in the CK was applied). Both biochar and straw improved soil aggregate stability that reflected by the mean weight diameter (MWD) and geometric mean diameter (GMD). Compared to the CK treatment, the BC treatment enhanced humic carbon (HMC) both in bulk soil and different aggregate fractions. Biochar decreased the humic acid carbon (HAC) in bulk soil compared to the initial content, but no differences were observed between BC and CK after the eight-year field experiment. All of the aggregate-associated HAC contents were significantly enhanced in response to BC treatment. SR was an effective way to improve soil organic carbon (SOC) and humic substances in bulk soil and aggregate fractions. SR had a relatively small effect on the relative proportions of the C functional groups. Solid-state 13C cross-polarization magic-angle-spinning nuclear magnetic resonance (CPMAS-NMR) spectra of bulk soils revealed that biochar increased the proportion of aromatic C. The ratios of alkyl C/O-alkyl C, aromatic C/aliphatic C, and hydrophobic C/hydrophilic C increased in response to the BC treatment compared to the other treatments. Taken together, biochar amendment can enhance soil aggregate stability, aggregate-associated HMC and stability of SOC on the scale of an eight-year field experiment. Biochar could be an effective approach to sequestrate carbon and improve the quality of brown earth soil.